PENENTUAN AKTIVITAS ANTIOKSIDAN Garcinia dulcis (Roxb.) Kurz, Blumeamollis (D.Don)Merr., Siegesbeckia orientalis L., DAN Salvia riparia H.B.K YANG DIKOLEKSI DARI TAMAN NASIONAL GUNUNG MERAPI DENGAN METODE DPPH(2,2-DIFENIL-1-PIKRIL-HIDRAZIL) SERTA PROFIL - Djoko Santosa; Perdana Priya Haresmita (Majalah Obat Tradisional, 2015)
This study was conducted to determine antioxidant activity of methanolic extract and wasbenzen extract of four plants species: Garcinia dulcis (Roxb.) Kurz, Blumea mollis (D.Don) Merr., Siegesbeckia orientalis L. and Salvia riparia H.B.K. These four plants species were collected from TNGM, based on DPPH free radicals capturing and the profile of its thin layer chromatography. Sample was extracted by gradual maceration process with wasbenzen and methanol. Antioxidant activity was analyzed by DPPH and qualitative analysis was done by thin layer chromatography (TLC) to determine the highest antioxidant activity. Antioxidant activity was showed by IC50 values and qualitative analysis of the data is presented in the chromatogram. The results shows that the highest antioxidant activity was the extract of Garcinia dulcis (Roxb.) Kurz  for both methanol and wasbenzene extract with IC50 value 38.613µg/mL and 139.381µg/mL respectively. Qualitative analysis of methanolic extract of Garcinia dulcis (Roxb.) Kurz by thin layer chromatography (TLC) showed that the extract contain of phenols and flavonoids.